Optimalisasi Strategi Pembelajaran Pendidikan Islam Melalui Pendekatan Saintifik - Nurjannah Nurjannah; Dwika Putri Adinda; Gusmaneli Gusmaneli (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This article explores the optimization of Islamic Religious Education (PAI) learning strategies through a scientific approach as an effort to improve integrative, reflective, and contextual learning quality. The scientific approach comprising five main steps: observing, questioning, reasoning, experimenting, and communicating plays a significant role in shaping students who not only cognitively understand Islamic teachings but also internalize spiritual values through critical and scientific thinking processes. This study employs a library research method by reviewing academic literature and relevant previous studies. The findings reveal that the scientific approach is effective in enhancing the quality of Islamic education, although its implementation faces several challenges, such as limited pedagogical competence among teachers, insufficient learning facilities, and resistance to critical thinking in religious education. Therefore, comprehensive optimization strategies including teacher capacity development, the design of scientific-based learning tools, technological integration, and the creation of a school culture that supports active and reflective learning are urgently needed. This article emphasizes that the scientific approach does not secularize religious learning but rather serves as a means to integrate faith and reason in shaping rational, religious, and adaptive Muslim generations.